2020
DOI: 10.1016/j.avsg.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Patients with a Ruptured Abdominal Aortic Aneurysm Are Better Informed in Hospitals with an “EVAR-preferred” Strategy: An Instrumental Variable Analysis of the Dutch Surgical Aneurysm Audit

Abstract: Background: While several observational studies suggested a lower postoperative mortality after minimal invasive endovascular aneurysm repair (EVAR) in patients with a ruptured abdominal aortic aneurysm (RAAA) compared to conventional open surgical repair (OSR), landmark randomized controlled trials have not been able to prove the superiority of EVAR over OSR. Randomized controlled trials contain a selected, homogeneous population, influencing external validity. Observational studies are biased and adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“… 26 However, the actual clinical decision in octogenarians regarding the surgical procedure when both EVAR and OSR are suitable could be dependent on local or regional setting as well. 27 Surprisingly, our study showed that despite the increased use of EVAR, the perioperative mortality rates of octogenarians and all patients were stable over the years, which was in contrast with previous studies. 1 , 28 A possible explanation for these stable mortality rates could be that due to the increased application of EVAR, relatively more frail patients have received treatment for an rAAA during the study period, which could have influenced perioperative mortality rates.…”
Section: Discussioncontrasting
confidence: 99%
“… 26 However, the actual clinical decision in octogenarians regarding the surgical procedure when both EVAR and OSR are suitable could be dependent on local or regional setting as well. 27 Surprisingly, our study showed that despite the increased use of EVAR, the perioperative mortality rates of octogenarians and all patients were stable over the years, which was in contrast with previous studies. 1 , 28 A possible explanation for these stable mortality rates could be that due to the increased application of EVAR, relatively more frail patients have received treatment for an rAAA during the study period, which could have influenced perioperative mortality rates.…”
Section: Discussioncontrasting
confidence: 99%